2021
DOI: 10.1002/mrm.28892
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry‐based reconstruction of real‐time cardiac MRI: Motion control and quantification of heart–lung interactions

Abstract: Purpose To test the feasibility of cardiac real‐time MRI in combination with retrospective gating by MR‐compatible spirometry, to improve motion control, and to allow quantification of respiratory‐induced changes during free‐breathing. Methods Cross‐sectional real‐time MRI (1.5T; 30 frames/s) using steady‐state free precession contrast during free‐breathing was combined with MR‐compatible spirometry in healthy adult volunteers (n = 4). Retrospective binning assigned images to classes that were defined by elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Previous RT-MRI studies during free-breathing demonstrated that even with calm breathing, respiration influences cardiac function [ 9 , 10 , 30 ]. The RV was especially affected significantly [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous RT-MRI studies during free-breathing demonstrated that even with calm breathing, respiration influences cardiac function [ 9 , 10 , 30 ]. The RV was especially affected significantly [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the heart position varied in images with equal respiratory bellows values resulting in greater movement from image to image in RT-MRI. MR-compatible spirometry could provide quantitative information on respiratory flow in future studies [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent introduction of a specific real-time MRI technique, fast low-angle shot technique 2.0 (FLASH 2.0), in two pediatric radiology departments in Germany has enabled such a high frame rate for daily routine evaluation [9] of moving organs such as the heart and joints, as well as for visualizing speech [10]. Of high clinical impact, this novel technique has recently been adopted to avoid motion artifacts in cranial MR examinations of non-sedated moving infants and young children [11].…”
Section: Why Is Real-time Mri For the Thorax Needed?mentioning
confidence: 99%